Graduates' Rational Choices in Seeking Job Opportunities via Digital Platforms in Buahbatu Village, Bandung Regency - Fahrul Alam Darsono; Bintarsih Sekarningrum; Desi Yunita (Labor Jurusan Sosiologi Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
The transformation of the digital economy has changed employment patterns in peri-urban areas, including Buahbatu Village, Bandung Regency, Indonesia. This study aims to analyze how secondary and higher education graduates make employment decisions through digital platforms amid limited access to formal employment opportunities. This research employs a descriptive qualitative approach using in-depth interviews, non-participant observation, and documentation involving ten graduate informants working in the informal digital sector. Data were analyzed using the interactive model of Miles and Huberman within the framework of James S. Coleman’s Rational Choice Theory. The findings show that graduates choose platform-based jobs such as freelancers, online resellers, content creators, and ride-hailing drivers as a form of adaptive rationality driven by economic needs, work flexibility, and limited access to formal labor markets. Social capital derived from family, peer networks, and digital communities plays an important role in providing job information, reducing uncertainty, and supporting adaptation to the digital economy. The study also finds that platform-based work has undergone a process of social normalization and legitimacy at the local level, where it is increasingly recognized as a valid form of employment. The novelty of this study lies in explaining graduate adaptive rationality in a peri-urban village context shaped by structural constraints in the formal labor market, strengthened digital social capital, and a gradual social legitimation process that transforms platform work from informal activity into socially recognized employment. Overall, digital employment decisions reflect not only economic considerations but also interactions between social structures, relational networks, and evolving work values in the digital era.